Nutrition in decompensated liver disease: A regional trainee-led audit investigating patient nutrition and outcomes following admission with decompensated chronic liver disease. (October 2022) - Morgan, J.A.; O'Flynn, L.; Mahgoub, S.; McFarlane, M.; Burch, N.; Gordon, V.; ,
Summary: Objective: To conduct a regional audit assessing the prevalence and management of malnutrition in decompensated liver disease. Method: All adults admitted with decompensated cirrhosis over one-month period to participating trusts were included. Malnutrition was identified using MUST and Royal Free Hospital-Nutritional Prioritisation Tool (RFH-NPT). Results: 47 patients were identified. The prevalence of malnutrition was 76.6%. This was independent of age (<65 versus ≥65; p = 1) or aetiology of liver disease (alcohol-related versus not; p = 0.55). Screening was significantly higher on Gastroenterology wards than other wards (77% versus 23%; p = 0.012). RFH-NPT identified 76.6% of patients as malnourished whereas MUST identified 55.3%. Supplementation was prescribed to 83% of eligible patients. 80% was oral supplementation and 20% received NG feeding. Median length of stay (9 (2–62) days) was higher in those prescribed supplements (11 vs 7 days, p = 0.041). Readmission rates were similar regardless of supplementation. Mortality was higher in malnourished patients (p = 0.03) and in those prescribed nutritional supplements at 1, 3 and 6 months (p = 0.026, p = 0.026 and p = 0.008) respectively, who were more likely to have severe liver disease. Conclusion: Prevalence of malnutrition is high in patients with decompensated cirrhosis but independent of age and aetiology and associated with higher Child-Pugh scores. The RFH-NPT was a more sensitive screening tool than MUST. Increased nutritional screening was noted on gastroenterology wards with more intervention in those with severe liver disease. Despite the study's limitations, once malnourished, nutritional intervention did not appear to impact on patient readmission or mortality rates therefore, we propose addressing malnutrition by utilising specialty dietician involvement at an earlier stage.